Analyzing Spotify User Experience using UEQ and Fuzzy K-Means Clustering - Chinta, Caroline Amanda; Fibriani, Charitas (STMIK Banjarbaru, 2025)
This study evaluates the user experience (UX) of Spotify using the User Experience Questionnaire (UEQ) and Fuzzy K-Means clustering. The main issue addressed is the need to understand user satisfaction, especially related to reliability. The objective is to assess Spotify’s UX quality and group users based on satisfaction. A total of 128 participants completed the UEQ, covering six dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. Results show five dimensions rated as “Excellent,” while Dependability was rated “Below Average,” indicating issues with control and consistency. Clustering analysis identified three user groups with different satisfaction levels. One cluster consistently reported low ratings across all dimensions. These findings reflect Spotify’s overall strong UX, while also pointing out areas for improvement. The integration of UEQ and clustering provides valuable insights into user segmentation and can serve as a framework for future UX evaluations. Keywords: Clustering; Fuzzy K-Means; Spotify; UEQ; User Experience AbstrakPenelitian ini mengevaluasi pengalaman pengguna (User Experience/UX) aplikasi Spotify menggunakan User Experience Questionnaire (UEQ) dan metode klasterisasi Fuzzy K-Means. Masalah utama yang dibahas adalah perlunya pemahaman terhadap kepuasan pengguna, khususnya dalam aspek keandalan. Tujuan penelitian ini adalah menilai kualitas UX Spotify dan mengelompokkan pengguna berdasarkan tingkat kepuasannya. Sebanyak 128 partisipan mengisi UEQ yang mencakup enam dimensi: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, dan Novelty. Hasil menunjukkan lima dimensi memperoleh nilai Excellent, sedangkan dimensi Dependability berada pada kategori Below Average, mengindikasikan adanya masalah dalam kontrol dan konsistensi. Analisis klaster menghasilkan tiga kelompok pengguna dengan tingkat kepuasan yang berbeda. Salah satu klaster secara konsisten menunjukkan penilaian rendah di semua dimensi. Temuan ini mencerminkan performa UX Spotify yang sangat baik secara umum, namun tetap ada aspek yang perlu ditingkatkan. Integrasi UEQ dan analisis klaster memberikan wawasan mendalam tentang segmentasi pengguna dan menjadi acuan untuk evaluasi UX selanjutnya.